Relationship between Leadership Styles of Nurse Managers and Staff Nurses Job Satisfaction in Public Hospital of Punjab, Pakistan - Naseem, Sofia; Afzal, Muhammad; Sehar, Sana; Gilani, Syed Amir (International Journal of Social Sciences and Management, 2018)
Introduction: Nurses are the “backbone” of any human services framework and their work is varied and extremely complicated. When carrying out their jobs, nurses faces different circumstances and patients, which are elements of the circumstances and patient level workloads. In addition, higher amount of nurse’s dissatisfaction prompts to leave out from the nursing profession. This generally creates staff shortage among nurses. Due to enhances extra time and job stress, increases burnout, longer patient holding up records, lastly, as an outcome expanded displeasure among patients Leadership is the way toward impacting representatives to accomplish organizational goals and objectives Methods: This analytical, cross-case study was conducted in public hospital of Lahore. Respondents ’selection was convenient sampling technique. Selected sample was 211 registered nurses. Well adopted questionnaire as per Likert scale was used in this study. Results: The finding of this study showed that caregivers prefer transformational styles of leaders to achieve optimal presentation of nurses. The results showed that there is statistically significance as p-value < 0.05 at all level of job satisfaction. Conclusions: A transformative leadership style promotes job satisfaction among nurses, which improves performance. Nurses job performance increased proportionally by increasing job satisfaction. In the current health system, it is necessary to develop leadership behaviors that have proven to be effective in the implementation of positive and adaptive behaviors among nurses. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 201-208